Pengetahuan Ibu dan Dukungan Suami terhadap Rendahnya Penggunaan Kontrasepsi Intra Uterine Device (IUD) - Retno, Sri Nowo; Wati, Tris Murning; Sulistiawati, Yuni; Veronica, Septika Yani (Jurnal Kesmas Asclepius, 2025)
The purpose of this study was to determine the relationship between maternal knowledge and husband's support with the use of Intra Uteri Device (IUD) contraception in the Bumi Nabung Health Center work area, Central Lampung Regency in 2024. This research method is a quantitative analytical study with a Cross Control approach. The population in this study were all Active KB Acceptors in the Bumi Nabung Health Center work area totaling 4,162, with a sample size of 192 acceptors consisting of 96 IUDs and 96 non-IUDs. Data collection using a questionnaire sheet. Univariate data analysis using frequency distrIbution, bivariate analysis using Chi Square. The results of the study showed that the frequency distrIbution of age characteristics was mostly >35 years (50.5%), multiparous parity (81.3%), secondary education (47.7%) and housewives (51%). Knowledge was mostly poor (54.2%), while IUD users were sufficient (67.7%). Non-IUD husband support was not supportive (68.8%), while IUD users received support from their husbands (70.8%). There is a significant relationship between maternal knowledge and the use of IUD contraception with a p value of 0.004 and an OR value of 2.478. There is a significant relationship between husband's support and the use of IUD contraception with a p value of 0.000 and an OR value of 5.343. From the results of the study, it can be concluded that the health center can prepare a health promotion program related to the use of IUDs according to the characteristics of mothers in their work area. Keywords: Husband Support, IUD, Knowledge.